"Just an Excuse People Are Just Using These Days": Attending to and Managing Interactional Concerns in Talk on Exclusion of Immigrants. (December 2017) - Sambaraju, Rahul; McVittie, Chris; Goodall, Karen; McKinlay, Andy
In line with discursive work on the role of constructions of minority groups in social exclusion, we offer an examination of talk on immigrants and its links with employment of British residents, in the U.K. Parliament and interview talk with British residents looking for work, in the context of a financial crisis (2007-2009). Discursive analysis of data shows that parliamentarians treat immigration as problematic for British residents' employment, whereas interviewees' responses reject or minimally accept this, while displaying sensitivity to the status of this as a prevalent complaint about immigration. Parliamentarians do so to warrant and challenge or manage challenges to Government's policies, whereas interviewees do so to manage being seen as discriminatory and work-shy. These findings show that constructions of immigration and its links with employment in the context of the financial crisis, and their use in warrants for exclusion are offered in ways to attend to the situated institutional and interactional relevancies in play for interlocutors.